Right partial rainbow refractometry for measuring droplet refractive index and size - Li, Can; Peng, Wenmin; Li, Tianchi; Li, Ning (Frontiers in Physics, 2023)
Rainbow refractometry can be employed for measuring the parameters of droplets or sprays. Considering the diversity of different measurement environments and droplet components, there are instances in experiments where optics fail to record the complete rainbow signal. To enhance the experimental data utilization, this paper investigates rainbow refractometry using the incomplete rainbow signal on the right side, focusing on its feasibility and accuracy. The concept that defines the incompleteness of the right-sided rainbow signal is termed as the dimensionless right signal partial ratio (RSPR). The study conducts a comprehensive analysis of refractive index, droplet diameter, and size distributions retrieved from the partial rainbow signals simulated by the Lorenz-Mie theory with varying RSPR values. For both partial standard and global rainbows, the critical value of the retrieval error is found to be whether the primary peak of the rainbow is preserved or not, i.e., RSPR=1. Laboratory experiments verify the feasibility and effectiveness of employing rainbow refractometry with right partial rainbow signals. The study addresses the challenge of incomplete recording of rainbow signals in experiments, and is expected to improve experimental efficiency and data utilization.